Reestablishment of Zamia lawsoniana (Zamiaceae, Cycadales), an endemic species of Mexico, with first description of the ovulate strobilus - Fernando Nicolalde-Morejón; Lilí Martínez-Domínguez; Marlon Aramis González-Aguilar; Dennis Wm. Stevenson (Acta Botanica Mexicana)
Background and Aims: Zamia, with 86 species, is the most diverse Neotropical cycad genus. In Mexico, 18 species occur, of which 15 are endemics. These taxa are distributed from sea level to 1200 m a.s.l. Recently, the phenology of Zamia in wild populations from southern Veracruz and Tabasco was studied to evaluate the morphological patterns of reproductive structures. While these records have been considered as Z. loddigesii, a species with a wide distribution along the Gulf of Mexico, different populations do possess morphological differences. Based on these data, we reevaluated the synonymy of Z. lawsoniana, which was described in 1884 and synonymized with Z. loddigesii in 1995.